PREVALENCE AND SPECIES IDENTIFICATION OF Pediculus humanus INFESTATION AMONG STUDENTS IN BOARDING SCHOOLS IN PALANGKA RAYA CITY - Arif Rahman Jabal; Deswita Wulandari; Ravenalla Abdurrahman Al Hakim Sampurna Putra; Arini Ratnasari; Dian Mutiasari (Journal of Vocational Health Studies, 2026)
Background: Across several continents, school-aged children, especially females, are frequently afflicted with pediculosis, an infectious disease caused by the parasite Pediculus sp., which feeds on human blood. Purpose: To identify the species and frequency of Pediculus sp. among pupils at boarding schools in Palangka Raya City. Method: This study used a descriptive-analytical cross-sectional design using a questionnaire as the main research instrument. Using a fine-toothed comb and ocular inspection, samples of Pediculus sp. were gathered. Five boarding schools in Palangka Raya City's Pahandut, Jekan Raya, and Sebangau subdistricts participated in the study. Data on pediculosis were described descriptively, and SPSS-16 was used to analyze the questionnaire responses. Result: Of the 121 students who participated in the survey, 39.6% had pediculosis and 60.4% did not. Compared to just 0.8% of male students, 38.8% of female students had the infection. Conclusion: Pediculus humanus capitis was the species of head lice found at Palangka Raya City's boarding schools. It was discovered that female pupils were more susceptible to pediculosis than male students. The Pediculus humanus capitis species' eggs, nymphs, and adult lice were found during inspection and identification. Notably, the sick students had stable socioeconomic circumstances, regularly bought toiletries, washed their hair properly, had decent personal hygiene, and showed sufficient understanding of pediculosis.